If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2 + X) = 8(2 + X) (2 * 9 + X * 9) = 8(2 + X) (18 + 9X) = 8(2 + X) 18 + 9X = (2 * 8 + X * 8) 18 + 9X = (16 + 8X) Solving 18 + 9X = 16 + 8X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8X' to each side of the equation. 18 + 9X + -8X = 16 + 8X + -8X Combine like terms: 9X + -8X = 1X 18 + 1X = 16 + 8X + -8X Combine like terms: 8X + -8X = 0 18 + 1X = 16 + 0 18 + 1X = 16 Add '-18' to each side of the equation. 18 + -18 + 1X = 16 + -18 Combine like terms: 18 + -18 = 0 0 + 1X = 16 + -18 1X = 16 + -18 Combine like terms: 16 + -18 = -2 1X = -2 Divide each side by '1'. X = -2 Simplifying X = -2
| n-3n=4 | | 4.30x=3.75x+4 | | a^3-7a^2-8a= | | .85x+.05(2-x)=.10(-31) | | a^3-7a^2-8= | | -10x+3x= | | 9g/3=6 | | 7x-3=78-2 | | x^2+32=4 | | 9-7(x+3)=5-6x | | h(x)=9x^5-12x^3+6x | | 25(4x+1)=9(10x+25) | | 9/10=99/x | | 4.0x+2=3.75x+4 | | 30=k(8) | | m+12.3=-4.1 | | 24x^2+24+6= | | 4p^2+4p-360= | | 5x+10-c=10 | | x-3/4=3/4 | | m+122.3=-4.1 | | 6x-8=2+9x | | 3=-3(7-2n)-4(n-7) | | 3(v+1)=2(v-8) | | 3234=2.1(x)+4.2(3x) | | 4b^2+36b= | | logx=10.23 | | 1/3x^2-2x=9 | | -9/20--3/5 | | x+13.4=-7.4 | | 7x-3x+12=4x-2x+20-4 | | 100*ln(x)=34 |